Determination of nickel in cigarettes smoke by molecular fluorescence - Talio, María Carolina; Luconi, Marta O.; Fernández, Liliana P. (Microchemical journal, 2011)
Smoking represents the main avoidable cause of disease and death in the world. Cigarette smoke contains over 4700 chemical compounds including 60 known carcinogens. The inhalation of tobacco smoke is one of the most significant sources of nickel exposure for occupationally unexposed population. The aim of this work was to evaluate nickel contents present in cigarette smoke by using an automatic sample preparation step and solid surface fluorescence. A total of 250 cigarettes (brands available in Argentine) were smoked in a smoking device applying vacuum and forcing the mainstream smoke to pass through a filter holder containing a Nylon membrane treated with eosin dye (eo). Nickel present in smoke cigarette was selectively retained by eo as an association compound. Chemically enriched nickel on nylon membranes was subsequent quantified by spectrofluorimetry (λem=545nm, λexc=515nm), reaching quantitative recovery with a detection limit of 1.56ngL−1 and quantification limit of 5.52ngL−1. The calibration sensitivity using zeroth order calibration was 1 1012ngL−1 (r2=0.9992) for the methodology with a linear range of 5.52 to 5.17 104ngL−1 Ni(II). Standard addition method was satisfactorily applied to nickel determination in mainstream smoke cigarettes of twenty brands. Results can be good correlated with urinary nickel contents coming from fifty subjects with different levels of addiction.